Adiponectin and AMP kinase activator stimulate proliferation, differentiation, and mineralization of osteoblastic MC3T3-E1 cells - Kanazawa, Ippei (BioMed Central, 2007)
BACKGROUND: Adiponectin is a key mediator of the metabolic syndrome that is caused by visceral fat accumulation. Adiponectin and its receptors are known to be expressed in osteoblasts, but their actions with regard to bone metabolism are still unclear. In this study, we investigated the effects of adiponectin on the proliferation, differentiation, and mineralization of osteoblastic MC3T3-E1 cells. RESULTS: Adiponectin receptor type 1 (AdipoR1) mRNA was detected in the cells by RT-PCR. The adenosine monophosphate-activated protein kinase (AMP kinase) was phosphorylated by both adiponectin and a pharmacological AMP kinase activator, 5-amino-imidazole-4-carboxamide-riboside (AICAR), in the cells. AdipoR1 small interfering RNA (siRNA) transfection potently knocked down the receptor mRNA, and the effect of this knockdown persisted for as long as 10 days after the transfection. The transfected cells showed decreased expressions of type I collagen and osteocalcin mRNA, as determined by real-time PCR, and reduced ALP activity and mineralization, as determined by von Kossa and Alizarin red stainings. In contrast, AMP kinase activation by AICAR (0.01–0.5 mM) in wild-type MC3T3-E1 cells augmented their proliferation, differentiation, and mineralization. BrdU assay showed that the addition of adiponectin (0.01–1.0 μg/ml) also promoted their proliferation. Osterix, but not Runx-2, appeared to be involved in these processes because AdipoR1 siRNA transfection and AICAR treatments suppressed and enhanced osterix mRNA expression, respectively. CONCLUSION: Taken together, this study suggests that adiponectin stimulates the proliferation, differentiation, and mineralization of osteoblasts via the AdipoR1 and AMP kinase signaling pathways in autocrine and/or paracrine fashions.